The helminth parasite community of European badgers (Meles meles) in Ireland. (2020) - Byrne, R.L.; Fogarty, U.; Mooney, A.; Harris, E.; Good, M.; Marples, N.M.; Holland, C.V.
Abstract: The European badger ( Meles meles ) is Ireland's largest terrestrial carnivore. Since first being identified as a wildlife reservoir of bovine tuberculosis in 1974 there has been an increased research focus into the behaviour of these ecologically important mammals in the Republic of Ireland (ROI). However, to date there has never been an assessment of the helminth parasite community of Irish badgers. This study of 289 badgers found helminth infection to be endemic within the sample population and we report for the first time the prevalence, abundance, intensity and aggregation of helminth infection in ROI. Eight distinct helminth taxa were recorded: Aelurostrongylus falciformis, Crenosoma melesi, Eucoleus aerophilus, Species A, Strongyloides spp., Uncinaria criniformis, and two unidentifiable but morphologically distinct nematodes. All helminths belong to the taxon Nematoda, and this is the first report of an exclusively nematode community across the badger's Eurasian distribution. Infection was not significantly influenced by the host sex, region of origin or season of sampling.